ANALISIS PENGARUH DER DAN TAT TERHADAP ROE PADA PERUSAHAAN MANUFAKTUR SUB-SEKTOR FARMASI DI BURSA EFEK INDONESIA TAHUN 2008-2012 - Sarikadarwati Sarikadarwati; Nina Afriati (Jurnal ACSY : Jurnal Accounting Politeknik Sekayu, 2016)
The final report entitled “Analysis The Influence of DER and TATon ROE at Manufacturing Sub-Sector Pharmacy Companies Listed in Indonesia Stock Exchange In Year 2008-2012”. This study aims to identify and analyze Working Debt to Equity (DER) and Total Asset Turnover (TAT) simultaneously and partically to Return On Equity (ROE) at Manufacturing Sub-Sector Pharmacy Companies Listed in Indonesia Stock Exchange In Year 2008-2012. The data used are secondary data form the financial statements of Manufacturing Sub-Sector Pharmacy Companies Listed in Indonesia Stock Exchange In Year 2008-2012. The analytical method that used is multiple linear regression. The analysis technique used are the descriptive statistic analysis, data test, multiple linear regression, and hypotheses test. The result is Debt to Equity (DER) and Total Asset Turnover (TAT) simultaneously significant effect to Return On Equity (ROE). Whereas partically Debt to Equity (DER) has negative significant effect to Return On Equity (ROE), but Total Asset Turnover (TAT) hasn’t effect to Return On Equity (ROE).